2005
DOI: 10.4049/jimmunol.174.7.4373
|View full text |Cite
|
Sign up to set email alerts
|

Protective CD8 T Cell Immunity Triggered by CpG-Protein Conjugates Competes with the Efficacy of Live Vaccines

Abstract: In contrast to infectious (live) vaccines are those based on subunit Ag that are notoriously poor in eliciting protective CD8 T cell responses, presumably because subunit Ags become insufficiently cross-presented by dendritic cells (DCs) and because the latter need to be activated to acquire competence for cross-priming. In this study, we show that CpG-Ag complexes overcome these limitations. OVA covalently linked to CpG-DNA (CpG-OVA complex), once it is efficiently internalized by DCs via DNA receptor-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 48 publications
9
79
0
3
Order By: Relevance
“…The dose of 10 mg antigen per injection was based on previous studies that also reported strong induction of cytotoxicity by both stable conjugates as well as mixtures of antigen and adjuvant. 10,11 In our study, very high cytotoxicity of 99% was observed following vaccination of the mice with the conjugates as well as a boost injection of the conjugates after 3 weeks. The strong cytotoxicity induced by SS comparable to both HYN and HYN-SS that was higher than that induced by the mixture of CpG and OVA was unexpected.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The dose of 10 mg antigen per injection was based on previous studies that also reported strong induction of cytotoxicity by both stable conjugates as well as mixtures of antigen and adjuvant. 10,11 In our study, very high cytotoxicity of 99% was observed following vaccination of the mice with the conjugates as well as a boost injection of the conjugates after 3 weeks. The strong cytotoxicity induced by SS comparable to both HYN and HYN-SS that was higher than that induced by the mixture of CpG and OVA was unexpected.…”
Section: Discussionmentioning
confidence: 49%
“…9,11 We hypothesize that if the antigen adjuvant components of the conjugate are released from each other once the conjugate has entered, the cell the antigen and adjuvant will be more readily available for processing. In this study we describe the enhancement of the immune response of the OVA-CpG conjugate when the OVA and CpG are linked via a disulphide bond that was shown in vitro to be specifically cleaved by the higher intracellular GSH concentration of the cytosol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Со-вместное введение, комплексирование антигена и CpG-ОДН может оптимизировать индукцию антиген-специфического иммунного ответа [16]. Кроме того, для повышения адъювантной активности CpG-ОДН компоненты вакцины возможно вводить в комплексе с различны-ми носителями: наночастицами, микросфера-ми, липосомами, что способствует активации сильного антиген-специфического иммунного ответа [31].…”
Section: Cpg-днк как перспективный адъювантunclassified
“…Differential expression of receptors might allow targeting of select DC subsets and ''tailor-made'' immunization [19,20]. Effective immunization was also observed following delivery of TLR ligand-antigen conjugates, which contain the maturation stimulus but are not as precise in cell targeting [21]. Although the in situ targeting strategy is clearly a promising approach, one caveat is that in diseased patients, DC subsets and precursors as well as their receptor expression may be variable and even abnormal so that translation into the clinic might hold unexpected surprises.…”
Section: Tumor Vaccines Must Exploit the Immunogenic Function Of DCmentioning
confidence: 99%